Engineering behavior and geotechnical challenges of sulfate-rich soils in Astana - Sagidullina, Nazerke; Satyanaga, Alfrendo; Kim, Jong; Moon, Sung-Woo (Frontiers in Built Environment, 2025)
This study investigates the engineering properties of sulfate-containing soils from Astana, Kazakhstan, with a focus on their physical, chemical, and water retention characteristics. Understanding the challenges posed by sulfate-rich soils is critical for developing effective stabilization methods, especially in regions with extreme climates. Initial soil characterization revealed that the soil is well-graded sand with silt (SW-SM), with significant sulfate content (8518.8 ppm) and salinity (18.45%). Advanced techniques, including ion chromatography (IC), X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM), identified the presence of sulfate minerals such as gypsum and anhydrite. The soil water characteristic curve (SWCC) demonstrated bimodal behavior, with distinct air entry values of 4.988 kPa for macropores and 1000 kPa for micropores, highlighting its complex water retention properties. Shrinkage tests, analyzed using a 3D scanner, revealed a hyperbolic drying curve, with a sharp void ratio reduction during the normal shrinkage phase and minimal changes during the residual phase. These results underscore the soil’s susceptibility to volumetric changes under varying moisture conditions. This comprehensive geotechnical characterization provides critical insights into the behavior of sulfate-rich soils and their implications for infrastructure stability. The findings emphasize the need for tailored engineering solutions to mitigate risks associated with sulfate-induced swelling and shrinkage, offering practical contributions to construction practices in sulfate-affected regions. Future research will explore stabilization strategies to enhance the mechanical performance and durability of these soils.